Copper-catalyzed aminooxygenation of N-allylamidines with PhI(OAc)2 - Sanjaya, Stephen (2013)
A Cu-catalyzed aminoacetoxylation of N-alkenylamidines has been achieved using PhI(OAc)2 as an oxygen source for synthesis of 4-acetoxymethyl-4,5-dihydroimidazoles, which could be further converted into 2,3-diaminopropanol derivatives using AlH3 as a reductant.